2009
DOI: 10.1093/glycob/cwp168
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated glycan inhibition of human hepatocellular carcinoma cell migration through binding to chemokine receptors

Abstract: SMMC-7721 hepatocellular carcinoma cells (HCC) were incubated with fucosylated glycoproteins that had been isolated from retinoic acid-treated cells by affinity chromatography. HCC migration was significantly inhibited by AAL- and LCA-glycoproteins. Glycopeptides, obtained by digestion of the glycoproteins with trypsin and papain, were found to have a similar inhibitory effect on HCC migration as the corresponding glycoproteins. The inhibitory actions of the glycoproteins were almost abolished after digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Fucosylation of GP73 is reported to be increased in patients with HCC [33]. A previous study suggested that fucosylation plays an important role in the interaction between interleukin-8 and its receptor, thereby inducing the migration of cancer cells in HCC [34]. Our current results suggest that fucosyl GM1 is a candidate hepatic CACAs biomarkers.…”
Section: Discussionsupporting
confidence: 63%
“…Fucosylation of GP73 is reported to be increased in patients with HCC [33]. A previous study suggested that fucosylation plays an important role in the interaction between interleukin-8 and its receptor, thereby inducing the migration of cancer cells in HCC [34]. Our current results suggest that fucosyl GM1 is a candidate hepatic CACAs biomarkers.…”
Section: Discussionsupporting
confidence: 63%
“…Accumulating evidences have demonstrated that aberrant glycosylation is the result of alterations in glycosyltransferases that may lead to cancer development and progression [ 9 - 10 ]. Fucosylation, one of the most important types of glycosylation, is regulated by fucosyltransferases (FUTs), which catalyse the transfer of the fucose (Fuc) residue from GDP-fucose donor substrate to acceptor substrates present on oligosaccharides, glycoproteins and glycolipids [ 11 - 13 ]. Deficiency or enhanced expression of FUTs has been reported in various cancers, and associated with cancer progression and metastasis [ 14 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…FUT7 modifies the apoptosis in human hepatocarcinoma cells. FUT8 is upregulated in human hepatoma cell line [ 11 , 14 , 16 - 18 ]. Thus, these results suggest that FUTs may play an important role in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, human neutrophils have 2 neutrophil-bound receptors for the endothelium-bound cytokines CXCR1 and CXCR2, whereas murine neutrophils have only CXCR2 [47]. CXCR2 has been thought to have 2 N-glycan sites [48], to be sensitive to enzymatic deglycosylation, which affects its normal function [49] and has been hypothesized to carry either a(1,2)or a(1,3)-fucose residues [50], which lends credence to our theory that the a(1,3) fucose may affect CXCR2 function. Also, endothelial CXCR2 has been implicated in the regulation of lung endothelial leakiness upon LPS stimulation [28] which may serve to explain why the ratio of Fut4 2/2 Fut7 2/2 :WT cells recovered was higher in the WT recipients (Fig.…”
Section: Discussionmentioning
confidence: 99%